Rahmah El Yunusiyah and the Transformation of Muslim Women's Education in Indonesia - Syahruddin Syahruddin; Syafril Syafril; Bukhari Bukhari; Nofrizal Nofrizal; Desi Asmaret; Sri Wahyuni; Riki Rahman (Suluah Pasaman, 2026)
This study analyzes the educational thinking of Rahmah El Yunusiyah and her contribution to the transformation of Muslim women's education in Indonesia. Against the backdrop of limited access to education for Muslim women in the early 20th century due to patriarchal social and cultural constructs, Rahmah El Yunusiyah founded Diniyyah Puteri in 1923. She introduced an Islamic educational model that integrated religious knowledge, general knowledge, character building, and life skills, making her a significant pioneer. This study uses library methods with a historical and descriptive-critical approach. The findings show that Rahmah's thinking, shaped by the Minangkabau context, the Islamic renewal movement, and personal experience, focuses on women's empowerment through holistic and integrative education. Its implementation in Diniyyah Puteri includes a comprehensive curriculum, emphasizing character education, independence, and women's leadership. Rahmah's thinking has proven to be relevant both historically and contemporary, aligning with the challenges of the digital era, Society 5.0, and the achievement of the Sustainable Development Goals (SDGs), particularly in realizing gender equality and sustainable development. Her intellectual legacy provides a crucial reference for the development of inclusive and progressive Islamic education.